Measuring the Job Satisfaction of Digital Library Professionals Workin in the Arts College Libraries in Coimbatore City (Global Journal of Human-Social Science, 2013)
Digital devices are presently at the centre of development in all of fields Libraries are currently undergoing profound changes due to digitization Job satisfaction is an important area to determine the view of the library professionals towards their job in the library The study has been under taken to measure the level of job satisfaction of digital library professionals in Coimbatore city and how the job facets affect on job satisfaction of library professionals do The study shows independence variety of work social status of the job supervision-human relation supervision technical moral values authority ability utilization library policies and practices scope of advancement relation with co workers recognition of job done and achievement has significant effect on job satisfaction Furthermore it noticed respondents are less satisfied at their job Finally the significant recommendations have been put forth to improve the level of job satisfaction of digital library professionals in Coimbatore city
Keywords: job satisfaction; digital library; digital environment; occupational stress; library professionals